Does the quality of safetalk motivational interviewing counseling predict sexual behavior outcomes among people living with HIV?. Issue 1 (January 2017) - Grodensky, Catherine; Golin, Carol; Parikh, Megha A.; Ochtera, Rebecca; Kincaid, Carlye; Groves, Jennifer; Widman, Laura; Suchindran, Chirayath; McGirt, Camille; Amola, Kemi; Bradley-Bull, Steven
Highlights: Studied MI quality and unprotected sex in SafeTalk trial with HIV positive patients. Higher MI quality per MISC coding predicted less unprotected sex at 8 months. Client-rated MI quality had mixed results; some higher ratings predicted more sex. Higher client-rated perceived benefit predicted less unprotected sex. More research needed to explore/enhance MI quality in intervention dissemination. Abstract: Objective: Although past research has demonstrated a link between the quality of motivational interviewing (MI) counseling and client behavior change, this relationship has not been examined in the context of sexual risk behavior among people living with HIV/AIDS. We studied MI quality and unprotected anal/vaginal intercourse (UAVI) in the context of SafeTalk, an evidence-based secondary HIV prevention intervention. Methods: We used a structured instrument (the MISC 2.0 coding system) as well as a client-reported instrument to rate intervention sessions on aspects of MI quality. Then we correlated client-reported UAVI with specific counseling behaviors and the proportion of interactions that achieved MI quality benchmarks. Results/Conclusion: Higher MISC-2.0 global ratings and a higher ratio of reflections to questions both significantly predicted fewer UAVI acts at 8-month follow-up. Analysis of client ratings, which was more exploratory, showed that clients who rated their sessions higher in counselor acceptance, client disclosure, and relevance reported higher numbers of UAVIs, whereas clients who selected higher ratings for perceived benefit were more likely to have fewer UAVI episodes. Practice implications: Further research is needed to determine the best methods of translating information about MI quality into dissemination of effective MI interventions with people living with HIV.